2021
DOI: 10.1177/01622439211026016
|View full text |Cite
|
Sign up to set email alerts
|

Disagreement and Agonistic Chance in Peer Review

Abstract: The purpose of grant peer review is to identify the most excellent and promising research projects. However, sociologists of science and STS scholars have shown that peer review tends to promote solid low-risk projects at the expense of more original and innovative projects that often come with higher risk. It has also been shown that the review process is affected by significant measures of chance. Against this background, the aim of this study is to theorize the notions of academic judgment and agonistic cha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(5 citation statements)
references
References 46 publications
(67 reference statements)
0
4
0
Order By: Relevance
“…It was presumably no coincidence that other interviewees also repeatedly used the word ‘crazy’ (01, physics, professor, 107; 12, biology, professor, 52; 19, physics, postdoc, 83; 20, physics, postdoc, 68; 21, biology, postdoc, 90; 27, physics, predoc, 42) to denote those research ideas that would have a better chance of being funded through a grant lottery (see also Roumbanis, 2021). ‘Crazy’ meant that the ideas clearly departed from previous research traditions and programs.…”
Section: Mitigating Field-specific Inconsistencies and Conflictsmentioning
confidence: 99%
See 1 more Smart Citation
“…It was presumably no coincidence that other interviewees also repeatedly used the word ‘crazy’ (01, physics, professor, 107; 12, biology, professor, 52; 19, physics, postdoc, 83; 20, physics, postdoc, 68; 21, biology, postdoc, 90; 27, physics, predoc, 42) to denote those research ideas that would have a better chance of being funded through a grant lottery (see also Roumbanis, 2021). ‘Crazy’ meant that the ideas clearly departed from previous research traditions and programs.…”
Section: Mitigating Field-specific Inconsistencies and Conflictsmentioning
confidence: 99%
“…(03, physics, professor, 58) I think [...] the random selection process can in fact break up structures, and that's what science thrives on -that we don't just always think in fixed patterns, that we instead want to break up structures, that we want to do new things. (16, biology, postdoc, 150) It was presumably no coincidence that other interviewees also repeatedly used the word 'crazy ' (01, physics, professor, 107; 12, biology, professor, 52; 19, physics, postdoc, 83; 20, physics, postdoc, 68; 21, biology, postdoc, 90; 27, physics, predoc, 42) to denote those research ideas that would have a better chance of being funded through a grant lottery (see also Roumbanis, 2021). 'Crazy' meant that the ideas clearly departed from previous research traditions and programs.…”
Section: Field-specific Legitimatementioning
confidence: 99%
“…His argument that studying luck can ‘balance skewed neoliberal narratives about individual efforts and achievement’ (p. 209) resonates with other recent accounts of the ‘myth’ of meritocracy and the tendency of the successful to underestimate privilege in their success ( Frank, 2016 ; Power et al, 2016 ). Other work theorizing luck has sought to disaggregate luck, chance, and serendipity by defining the different forms these can take ( Yaqub, 2018 ): Both Roumbanis (2021) and Sand and Jongsma (2020) , for instance, discuss different types of chance or luck, in terms that are tied to the contexts in which they emerge.…”
Section: Luck In the Context Of Sciencementioning
confidence: 99%
“…Severin and Chataway (2021a) explored causes and effects of reviewer overburdening and found that scholars, referees, editors, and publishers believe that the reviewing workload has become unbearable, that the workload is distributed unequally among scholars, and that overburdening is caused by an increase in manuscript submissions, insufficient editorial triage, lack of reviewing instructions, difficulties in recruiting reviewers, inefficient manuscript handling, and a lack of institutionalization of peer review. Roumbanis (2021) theorized how panels struggle to reach a consensus decision when there is strong disagreement among panelists. He calls the results of such struggles agonistic chance, that is, unforeseen consequences of social interactions in peer review.…”
Section: Some Theoretical Efforts On Peer Reviewmentioning
confidence: 99%